Pengaruh Perputaran Piutang Usaha Terhadap Keuntungan Usaha Pada Umkm Koperasi Syariah Anugerah Batang Kuis - Edi Joko Saputra; Kartika Sari Lubis (CIVITAS: Jurnal Studi Manajemen, 2022)
The purpose of this study was to determine whether there is an effect ofreceivables turnover on profits at the Anugerah Batang Kuis Cooperative SMEs.Data analysis using simple linear regression test, hypothesis testing using thecoefficient of determination (R2), partial test (T test), while data processing usingthe SPSS 22 program. 8,730, and T-Test Results with a count of 3701 and Ttable2.13185, with a significant value of 0.000. Thus partially the receivables turnovervariable has a positive and significant effect on profits (profit).